1972
DOI: 10.4102/koedoe.v15i1.664
|View full text |Cite
|
Sign up to set email alerts
|

Observations on inshore and pelagic Dolphins on the South-Eastern Cape coast of South Africa

Abstract: The occurrence, size and seaward distribution of schools of inshore and pelagic dolphins is described for three study areas on the south-eastern Cape coast (Algoa Bay; the Tsitsikama Coastal National Park and Plettenberg Bay). Inshore dolphins {Tursiops and Sousa sp.) frequented the coastline in relatively small schools whereas pelagic dolphins {Delphinus delphis and Stenella caeruleoalba) occurred in very large schools far out to sea. Different ecological zones were used by Sousa for feeding and for social be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…There is no known gene flow between shortbeaked common dolphins and long-beaked common dolphins, and they occur sympatrically in tropical Cape coast of south Africa Saayman et al 1972 and temperate waters (Heyning & Perrin 1994;Rice 1998). In Santa Monica Bay, California, the direct sympatric ecology of short-beaked common dolphins and long-beaked common dolphins was investigated (Bearzi 2003).…”
Section: Bottlenose Dolphins and Indo-pacific Bottlenose Dolphinsmentioning
confidence: 99%
“…There is no known gene flow between shortbeaked common dolphins and long-beaked common dolphins, and they occur sympatrically in tropical Cape coast of south Africa Saayman et al 1972 and temperate waters (Heyning & Perrin 1994;Rice 1998). In Santa Monica Bay, California, the direct sympatric ecology of short-beaked common dolphins and long-beaked common dolphins was investigated (Bearzi 2003).…”
Section: Bottlenose Dolphins and Indo-pacific Bottlenose Dolphinsmentioning
confidence: 99%
“…Saayman, Bower & Tayler, 1972). One interesting possibility in the pelagic environment is for predation risk to be vertically strati®ed because of changes in light level and the vertical strati®cation of shark species.…”
Section: Odontocete Behavioural Responses To Shark Predation Riskmentioning
confidence: 99%
“…While cetaceans present particular methodological challenges (Mann ), activity budget data have shed light on the relationship between behavior and prey ecology, bathymetry, tidal state, time of day, season, and survival (Saayman et al . ; Shane , ; Ballance ; Bräger ; Hanson and Defran ; Mann and Watson‐Capps ; Steiner ). Several studies have also found links between cetacean activity budgets and human interactions and disturbances (Bejder et al .…”
mentioning
confidence: 99%